2017
DOI: 10.24136/eq.v12i4.35
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of payout policy and investment attractiveness of companies listed on the Warsaw Stock Exchange

Abstract: Research background: Making decisions concerning the payout policy depends on many diversified neoclassical and behavioral determinants. Although these factors are well-described in the literature, there is still a research gap concerning the lack of a comprehensive impact model of payout policy determinants on the investment attractiveness of shares. Purpose of the article: The aim of this paper is to present the diverse nature of the relation-ship between different forms of cash transfer to the shareho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There are many research papers dedicated to different aspects of the cost of equity capital (hereinafter referred to as CEC) management (see e.g., Michalak, 2016;Pieloch-Babiarz, 2017;Tomczak, 2017;Pustylnick, 2017;Dokulil et al, 2017). As a rule the internal factors and their impacts that are analysed by international scientists can be divided into several groups as corporate disclosure, corporate governance, social performance and other financial related performance.…”
Section: Introductionmentioning
confidence: 99%
“…There are many research papers dedicated to different aspects of the cost of equity capital (hereinafter referred to as CEC) management (see e.g., Michalak, 2016;Pieloch-Babiarz, 2017;Tomczak, 2017;Pustylnick, 2017;Dokulil et al, 2017). As a rule the internal factors and their impacts that are analysed by international scientists can be divided into several groups as corporate disclosure, corporate governance, social performance and other financial related performance.…”
Section: Introductionmentioning
confidence: 99%
“…The achievement of their investment goals is possible, in particular, after an investment decision as the consequence of analysis of not only the company's dividend policy (understood as a strategy of dividing the net profit into the part paid to shareholders in the form of dividend and part left in the company for development purposes), but also the company's financial condition. The financial standing of the company is not only an essential factor in making investment decisions, but also one of the determinants of conducting a dividend policy [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, the most important financial determinants of dividend payment include the following factors: a) liquidityaccording to the agency theory highly liquid companies pay out dividends to reduce agency costs [14]; b) profitabilitybased on the signaling theory, it should be indicated that companies that achieve high net profits may pay out dividends in order to send a positive signal to the market about their financial condition [12]; c) leveragea high debt increases the costs of external financing, and consequently also the risk of its operations. In addition, companies with high levels of indebtedness may be less inclined to pay dividends when they use the net profit to pay off their liabilities [7]; d) growth opportunitiesit is indicated that mature companies are more eager to pay out dividends due to lower investment opportunities and greater chances of obtaining cheaper capital for development [6]; e) company's sizeit has been proven that larger companies pay dividends relatively more often and of greater value [17]. It may be related to the stage of the company's life cycle, its development opportunities or the sector's maturity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analytical information, including those regarding the financial condition, not only allows efficient and effective day-to-day management of the entity, but also serves to make the right strategic decisions facilitating the development of the company in the future. They are also important for the company's stakeholders, in particular for current and potential investors (Pieloch-Babiarz, 2017;Pietrzak et.al. 2017).…”
Section: Introductionmentioning
confidence: 99%